Efektivitas Pencegahan Dan Penanggulangan Kriminalitas Melalui Patroli Polisi Di Kepolisian Sektor Pedamaran Timur Polres Ogan Komering Ilir - Marzuki, Marzuki; Lisdiana, Lisdiana; Islamy, Diah Putri (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2024)
The patrol efforts conducted by the East Pedamaran Sector Police of the Ogan Komering Ilir Police Department are expected to create a sense of security within the community and ensure that community activities run smoothly. Active participation from the community is also needed to achieve safety and comfort in their environment. Motorbike and car patrols are conducted through routes in vulnerable areas, tourist attractions, and during crime-prone hours, namely from 09:00 to 13:00 WIB when houses are usually left unattended by their owners, and from 22:00 to 03:00 WIB when homeowners are resting/sleeping, thus making the surroundings quiet. Therefore, these patrols are important for the prevention and mitigation of crime, especially in vulnerable areas. The purpose of this study is to analyze the effectiveness of crime prevention and mitigation through police patrols in the region. Several obstacles identified include a lack of budget support, damaged facilities and infrastructure, and an insufficient number of police officers conducting patrols. The data analysis technique used in this study is qualitative data analysis. The study results indicate that overall, crime prevention and mitigation through police patrols in the East Pedamaran Sector Police of the Ogan Komering Ilir Police Department have been effectively carried out, although there are still obstacles such as damaged facilities and infrastructure, a shortage of patrolling police officers, and a lack of budget support.